Combined plant proteins as fishmeal replacements in pearlspot (Etroplus suratensis): Effects on growth performance, digestive enzymes and fatty acid composition - E. P. Madhubabu; R. Jannathulla; H. Imran Khan; Y. Mohamed Thoufeek; K. Ambasankar; J. Syama Dayal (Indian Journal of Fisheries, 2025)
A mix of plant proteins (PP) (soybean meal, groundnut oilcake, wheat gluten meal and corn gluten meal in a 4:2:2:2 ratio) was used to partially replace fishmeal in the diets of pearlspot (Etroplus suratensis). Five iso-nitrogenous diets (301.20-306.85 g kg-1 crude protein) were prepared by substituting fishmeal at 0% (control, FM-R0), 25% (FM-R25), 50% (FM-R50), 75% (FM-R75) and 100% (FM-R100). The results revealed that the growth performance remained optimal up to 50% fishmeal replacement, beyond which significant declines were observed. Digestive enzyme activities varied significantly (p<0.05) with fishmeal substitution levels. Pepsin activity was highest at 50% replacement, while trypsin, chymotrypsin, carboxypeptidase A and B activities were comparable to the control. Pepsin activity was observed only in the stomach, whereas trypsin and chymotrypsin activities were detected in the liver, anterior intestine, and posterior intestine, with the highest activity reported in the posterior intestine Carcass composition in terms of moisture, protein, and ash was significantly influenced (p<0.05) by dietary changes, while other parameters remained unaffected. Fatty acids, in particular C20:4, C20:5, and C22:6 were significantly lower (p<0.05) in fish fed with higher PP (FM-R75, FM-R100). These results demonstrate that up to 50% of dietary FM can be effectively replaced with a PP blend in pearlspot juveniles without compromising growth, digestive enzyme activity, or carcass quality. Keywords: APU, Carcass composition, FCR, Gluten meal, Iso-nitrogenous diets, Pepsin activity, PER, SGR, Soybean meal